Optimization of Compost Mixing Efficiency and Airflow Through Innovative Gate Design in a Dual-Chamber Brick Tank System - Ari Saputra; Supli Effendi Rahim; Gusmiatun (Journal of Smart Agriculture and Environmental Technology, 2026)
The development of innovative composting systems based on appropriate technology is crucial in addressing the pressing environmental issue of organic waste management in Indonesia. This study aims to develop and test a two chamber composting system with innovative airflow gates to enhance the efficiency of organic waste processing. The system was tested using a completely randomized design with four different treatments: innovative system, standard machine, manual method, and natural method, each with three replications. The results showed that the innovative system with airflow gates achieved the fastest composting time of 20 days, with a stable pH range of 6.9-7 and optimal moisture content of 34-36%. The system also produced compost with high nutrient content, including organic carbon, phosphorus, and potassium. Additionally, the system reduced labor requirements by 93% compared to conventional methods. Soil analysis revealed that the use of compost from the innovative system significantly improved soil quality and reduced chemical fertilizer requirements by 25-50%. These findings demonstrate that the composting system with airflow gates is superior in producing high-quality compost consistently. This system also offers a sustainable solution for organic waste management in Indonesia. This innovation has great potential for widespread adoption as an effective and efficient solution for organic waste management. Further development of this system can make a significant contribution to environmental conservation efforts and agricultural productivity enhancement in Indonesia.